Experimental Evaluation of Mechanical Properties in Transmission Mechanisms of Electromechanical Actuators - Matteo Bertone; Edoardo Briano; Paolo Maggiore; Matteo D. L. Dalla Vedova (Engineering Proceedings, 2025)
The application of electromechanical actuators (EMAs) is experiencing significant growth across various industrial sectors, including the aerospace industry. This shift involves a transition from hydraulic to electric actuation, which promises to reduce the overall weight of aircraft while increasing system efficiency. However, the use of EMAs is currently limited to non-safety-critical functions due to the still limited understanding of their behavior. Accurate mathematical models are essential for analyzing their operation and interaction within complex systems. This study aims to present a methodology for simulating the behavior of motion transmission components under loads in static conditions. To achieve this, experimental data were collected from an existing test bench designed to enhance the elastoplastic effects within the motion transmission system. Preliminary analysis of these data enabled modifications to the model’s architecture to incorporate the compliance of the mechanical line. Subsequent fine-tuning of the parameters improved the correspondence with the real system’s response. The results indicate that the refined model could accurately simulate the behavior of electromechanical actuators under the specified conditions, providing a valuable tool for the design and optimization of these systems in industrial applications. Future work will focus on extending this methodology to dynamic conditions and validating the model against a wider range of operational scenarios.